The impact of buyer shopping orientations and demographic factors on the purchasing for different product types- in the context of online shopping - Haseba Salim Hamad (Zanco Journal of Humanity Sciences)
This study examines the impact of buyer shopping orientations and demographic factors on the purchasing for different product categories in the context of online shopping. To validate the study conceptual framework this research employs quantitative -method research in order to achieve the highest possible validity and reliability of the results. The quantitative data presented in this study were collected from an e-survey of consumers in the Kurdistan region/ Iraq using a self-administered questionnaire. This method was chosen, due to the fact that it is time and cost efficient compared to other distribution methods (Aaker et al. 2006). The sample consisted of 300 responses and was collected among consumers in the Kurdistan region/ Iraq. Structural equation modelling (SEM) was utilised to analyse the data collected. The findings show that the purchasing preferences vary by product category.